Fonologi perbedaan vokal - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2023)
Phonology contains elements of language that discuss elements. Understanding and mastering speaking skills is very important for students. Knowing the effectiveness of the use of learning in Indonesian phonology. Phonology is concerned with the process of conveying the sounds of language differently but still retaining the same meaning and context. This includes changing phonemes, varying intonation, changing vowels, consonants, or accents, and using different sentence structures while retaining the same meaning. Phonological is a way of expressing something with variations in sound, but still retaining the same message, The branch of linguistics that studies the sounds of language is generally called "phonology." Language plays a very important role in our daily life. Phonology includes elements of language as a means of human speech and is very important to be mastered by students to find out the effectiveness of the use of learning